PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM BERBANTUAN MICROSOFT TEAMS UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR AKUNTANSI - Anik Setyaningsih; siswandari siswandari; nurhasan hamidi (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2021)
AbstractThis reseacrh aims to (1 ) improve learning motivation with the implementation of the Flipped Classroom learning model assisted by Microsoft in the subject of Financial Accounting for class XI AKL 1 students of SMK in Sukoharjo and (2) improve learning outcomes with the implementation of the Flipped Classroom learning model assisted by Microsoft in the subject of Financial Accounting for class XI AKL 1 students of SMK in Sukoharjo. This research was a classroom action action conducted in two cycles. The research subjects were students of class XI AKL 1 which consisted of 36 students. Data collection used questionnaires and learning outcomes tests. The questionnaire validity testing used construct validity and the learning outcomes testing used content validity. The data analysis technique used comparative descriptive statistics and critical analysis techniques. The results of this research conclude that (1) the implementation of the Flipped Classroom learning model assisted by Microsoft Teams can improve the learning motivation in the subject of Financial Accounting for class XI AKL 1 students of SMK in Sukoharjo and (2) the implementation of the Flipped Classroom learning model assisted by Microsoft Teams can improve the learning outcomes in the subject of Financial Accounting for class XI AKL 1 students of SMK in Sukoharjo. The average percentage of learning motivation increased by 7.88 and learning outcomes increased by 9.03 in cycle II. This increase was statistically significant at α = 0.05 with t = 3.523 and sig. = 0.001 for motivation and t = 3.447 with sig. = 0.001 for learning outcomes.Keywords: Flipped Classroom, Microsoft Teams, Learning Motivation, Learning Outcomes AbstrakPenelitian ini bertujuan untuk (1) meningkatkan motivasi belajar dengan penerapan model pembelajaran Flipped Classroom berbantuan Microsoft Teams pada mata pelajaran Akuntansi Keuangan siswa kelas XI AKL 1 SMK di Sukoharjo dan (2) meningkatkan hasil belajar dengan penerapan model pembelajaran Flipped Classroom berbantuan Microsoft Teams pada mata pelajaran Akuntansi Keuangan siswa kelas XI AKL 1 SMK di Sukoharjo. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus. Subjek penelitian adalah siswa kelas XI AKL 1 yang terdiri dari 36 siswa. Teknik pengumpulan data penelitian menggunakan angket dan tes hasil belajar. Uji validitas angket menggunakan validitas konstruk dan tes hasil belajar menggunakan validitas isi. Analisis data menggunakan teknik statistik deskriptif komparatif dan analisis kritis. Hasil penelitian ini menyimpulkan bahwa (1) penerapan model pembelajaran Flipped Classroom berbantuan Microsoft Teams dapat meningkatkan motivasi belajar Akuntansi Keuangan siswa kelas XI AKL 1 SMK di  Sukoharjo dan (2) penerapan model pembelajaran Flipped Classroom berbantuan Microsoft Teams dapat meningkatkan hasil belajar Akuntansi Keuangan siswa kelas XI AKL 1 SMK di Sukoharjo. Rata-rata persentase motivasi belajar meningkat 7,88 dan hasil belajar meningkat 9,03 pada siklus II. Peningkatan ini signifikan secara statistik pada α = 0.05 dengan t= 3,523 sig.= 0,001 untuk motivasi dan t= 3,447 dengan sig.= 0,001 untuk hasil belajar.Kata Kunci: Flipped Classroom, Microsoft Teams, Motivasi Belajar, Hasil Belajar